Linear Regression with Non-Normal Error Terms - Zeckhauser, Richard; Thompson, Mark (The Review of Economics and Statistics, 1970)
JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. The MIT Press is collaborating with JSTOR to digitize, preserve and extend access to The Review of